Research Progress on Terahertz Quantum-Well Photodetector and Its Application - Shao, Dixiang; Fu, Zhanglong; Tan, Zhiyong; Wang, Chang; Qiu, Fucheng; Gu, Liangliang; Wan, Wenjian; Cao, Juncheng (Frontiers in Physics, 2021)
Compared with other typical terahertz (THz) detectors, the quantum well photo-detector (QWP) has the advantages of high detection sensitivity, fast response, mature fabrication, small size and easy integration. Therefore, it is suitable for high-speed detection and imaging applications at THz band. Researchers in the domestic and overseas have systematically studied the material design and device performance of THz QWP. The design of device peak frequency error is within 8%, the max peak responsibility is 5.5A/W, the fastest response speed is 6.2GHz, the best noise equivalent power: ~10-13 W/Hz0.5, and the spectrum range 2.5THz ~ 6.5THz. Firstly the article introduces the basic principles and theoretical calculations of THz QWP, and then summarizes the research progress of THz QWP in our research group at imaging and communication, and looks forward to its future development.